The amphibious murines of New Guinea (Rodentia, Muridae): the generic status of Baiyankamys and description of a new species of Hydromys - Helgen, Kristofer M. (Zootaxa, 2005)
The amphibious murine rodents of New Guinea have traditionally been classified in three genera: Hydromys E. Geoffroy, 1804, Parahydromys Poche, 1906, and Crossomys Thomas, 1907. Species currently classified in Hydromys can be further divided into two cladistic groups: species distributed in lowland habitats (below 2000 m) with glossy, dark brown dorsal pelage, and species restricted to upper montane rivers and lakes (generally above 2000 m) with soft, silvery grey dorsal pelage. These two groups differ not only in pelage traits and habitat association but also in craniodental and phallic anatomy. The generic-level name Baiyankamys Hinton, 1943, is resurrected for the latter cluster (which includes two species, B. shawmayeri of eastern New Guinea and B. habbema of west-central New Guinea). Additionally, a new species of Hydromys (H. ziegleri n. sp.) is described from the southern foothills of the Prince Alexander Range of Papua New Guinea. Mammalian zoogeography in the North Coast Ranges, an area of considerable geographicallyrestricted mammalian endemism, is reviewed.